Motional studies of one and two laser-cooled trapped ions for electric-field sensing applications. Issue 5 (30th March 2018) - Domínguez, F.; Gutiérrez, M. J.; Arrazola, I.; Berrocal, J.; Cornejo, J. M.; Del Pozo, J. J.; Rica, R. A.; Schmidt, S.; Solano, E.; Rodríguez, D.
Abstract: We have studied the dynamics of one and two laser-cooled trapped 40 Ca + ions by applying electric fields of different nature along the axial direction of the trap, namely, driving the motion with a harmonic dipolar field, or with white noise. These two types of driving induce distinct motional states of the axial modes: a coherent oscillation with the dipolar field, or an enhanced Brownian motion due to an additional contribution to the heating rate from the electric noise. In both scenarios, the sensitivity of an isolated ion and a laser-cooled two-ion crystal has been evaluated and compared. The analysis and understanding of this dynamics is important towards the implementation of a novel Penning trap mass-spectroscopy technique based on optical detection, aiming at improving precision and sensitivity.